STUDI SIFAT FUNGSIONAL DAN KIMIA TEPUNG KECAMBAH KACANG KORO BENGUK (Mucuna pruriens L.) - Liadi, Vivian Citra; Wisaniyasa, Ni Wayan; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
The purpose of this study was to determine the functional and chemical properties of mucuna bean sprout flour. This study was conducted using 48 hour germination and without germination of mucuna bean, and each treatment was repeated three times. Mucuna bean flour and mucuna bean sprouts flour were tested for rendemen, functional properties (water absorption, oil absorption, swelling volume, and solubility), and chemical properties (moisture content, ash content, protein content, fat content, carbohydrate content, and HCN content). The results showed that germination of mucuna bean had a very significant effect on rendemen, water absorption, oil absorption, ash content, moisture content, a significant effect on fat content, carbohydrate content, and had no significant effect on swelling volume, solubility, protein content, and HCN content. The results showed that rendemen of mucuna bean sprout flour was 63.93% (db), the functional properties of mucuna bean sprout flour were water absorption 1.67 ml H2O/g solid, oil absorption 2.17 ml oil/g solid, swelling volume 8.68 ml/g, and solubility 25.76%, while the chemical properties of mucuna bean sprout flour were water content 8.10%, ash content 2.87%, protein content 36.33%, fat content 10.77%, carbohydrate content 41.92%, and HCN content 5.39 mg/kg.